Relações públicas e sustentabilidade empresarial no Brasil : uma análise a partir das diretrizes atuais ESG e agenda 2030 - Silva, Liliane Fraga da (2022)
The study is based on the convergence of the fields of Public Relations and Corporate Sustainability. The general objective is focused on analyzing the possible relationships between Public Relations and Corporate Sustainability in Brazil, based on the current guidelines: ESG and the 2030 Agenda. The theoretical framework covers a contextualization of the theme of corporate sustainability, presenting a brief historical approach, main critical positions and favorable, conceptualization of the terms sustainability, corporate sustainability, social responsibility and corporate citizenship. It also presents the considered current guidelines. Different theoretical strands in the field of Public Relations, adopted from the perspective of this study, also make up the theoretical framework: the general theory of excellence (GRUNIG, 2011), the critical theory (PERUZZO, 1984; 1998; 2009), and the theory of political function (SIMÕES, 1995;2001;2009). The methodological procedure adopted is composed of the Bibliographic and Documentary Research techniques (GIL, 2010) (MARCONI; LAKATOS, 2010), for the bibliographic survey and data collection, and the Content Analysis (BARDIN, 2016), for data analysis. Two official documents make up the research analysis corpus: SDG Compass – The SDG guide for companies; and The Evolution of ESG in Brazil (2019/2020). The results obtained demonstrate that the main relationship established between Public Relations and Corporate Sustainability starts from the understanding that the relationship of organizations with their publics becomes the main asset of Corporate Sustainability. From this understanding, different possibilities of relationships arise from the dimensions of Public Relations, which are manifested through situations that arise.